Citizens' Contrasting Aspirations About Their Political System: Entrustment, Participation, Identification and Control - Bedock, Camille (Frontiers in Political Science, 2020)
Empirical political science has increasingly focused on citizens' conceptions of their political system. Most existing studies draw upon large quantitative datasets which have produced contradictory results. Qualitative approaches are used more and more commonly to identify the general narrative produced by ordinary citizens on their political system, but they tend to underplay the variations found in their discourses. In this article, I use semi-directed interviews to explore citizens' contrasting aspirations about their political system. This article is based on 32 interviews conducted with French citizens across Fall and Winter 2017 and on 24 interviews conducted during the Yellow Vests movement in fall 2019. During these interviews, citizens were asked to define in their own terms what politics is, what it should achieve, what the flaws and advantages of their political system are and what should be changed. These citizens have produced four ideal-typical discourses, uncovering four distinct conceptions of what the political system is, how it legitimizes itself, what types of procedures it should lay on and what types of outcomes it should produce. Citizens' discourses heavily focus on alternative logics of political representation, which remains unavoidable to channel political decisions. They express four competing aspirations: entrustment, participation, identification, and control & sanction. The two latter conceptions remain under-explored empirically.